Translating Chinese Calligraphy Into Indonesian: A Philological Approach - ., Julina; Erwani, Intan; ., Rudiansyah (KnE Social Sciences, 2023)
This paper is entitled ”Translating Chinese calligraphy into Indonesian: A Philological Approach.” Furthermore, the researcher intends to: (1) present a translation of Chinese calligraphy script in Indonesian, (2) express the moral message contained in Chinese calligraphy script. This study used a philological approach, which consisted of manuscript research methods and text editing, utilizing Lucien Goldman’s theory of philological explanation. Based on the Chinese calligraphy script found in Tjong A Fie’s mansion, the researchers made pragmatic structural observations and presented them from descriptive, analytical and comparative stages. The results of this study are the reconstruction of calligraphy characters as the content of the text that is abstract and essential; to be precise the Chinese calligraphy characters are found at the front gate, main entrance, front door and back right-wing of Tjong A Fie’s mansion. In this pragmatic observation of the Chinese calligraphy script, Chinese social and cultural values are obtained, such as the belief system, philosophy, and the relationship between humans and nature. These values are applied by the Chinese community as a guideline hence they can live in peace, harmony and balance. Keywords: Chinese Calligraphy; philological approach; Chinese community